2023
DOI: 10.3389/feduc.2023.1108542
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and writing anxiety as predictors of Iranian EFL learners’ performance in IELTS writing module: a multi-dimensional perspective

Abstract: This study aimed to investigate the relationship between Iranian EFL Learners’ perfectionism and writing anxiety and their performance in the IELTS Writing Module. To this end, sixty-eight Iranian EFL learners were selected via convenience sampling. Multidimensional Perfectionism Scale developed and validated by Hewitt and Flett (1991) and Second Language Writing Anxiety Inventory devised by Cheng (2004) were administered to the participants. The participants were then asked to write on an assigned topic from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…So, they experience a high sense of anxiety. This agrees with the results of the previous study proposing that those language learners pursuing an idealized rather than a realistic pro ciency level have more potential to experience higher language learning anxiety (Khosravi et al, 2023). The positive beta coe cient implies a direct and proportional relationship, suggesting that the more perfectionistic tendencies an individual possesses, the greater the likelihood of elevated listening anxiety.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…So, they experience a high sense of anxiety. This agrees with the results of the previous study proposing that those language learners pursuing an idealized rather than a realistic pro ciency level have more potential to experience higher language learning anxiety (Khosravi et al, 2023). The positive beta coe cient implies a direct and proportional relationship, suggesting that the more perfectionistic tendencies an individual possesses, the greater the likelihood of elevated listening anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…The former, always are worried about being judged by others and de ned by a high standard for their learning achievements, and the latter usually are more relaxed and have less worry over the ideas of others (Gregersen & Horwitz, 2002). Khosravi et al (2023) asserted that the relationship between perfectionism and LA is de nite and learners with a high level of perfectionism experience a greater level of FL anxiety.…”
Section: The Relationship Among La Srl and Perfectionismmentioning
confidence: 99%
“…In the study of Lababidi (2021) about the writing anxiety among freshmen Lebanese EFL learners it was also found that 53 percent of the participants suffered from perfectionism. Finally, Khosravi et al (2023) reported no association JELTL (Journal of English Language Teaching and Linguistics), 8(3), 2023 between perfectionism and writing performance among Iranian English translation students in performing IELTS writing tasks, while they indicated a significant negative relationship between writing anxiety and writing performance in the study.…”
Section: Perfectionism and Writing Anxietymentioning
confidence: 68%
“…However, whether gender determines anxiety in writing can be caused by some factors, such as social expectations and gender roles (Al-Kubaisy et al, 2020;Cocuk et al, 2016;Hz, 2022), stereotypes (Hz, 2022;Rodríguez et al, 2009), negative feedback (Al-Kubaisy et al, 2020), perfectionism (Khosravi et al, 2023), and lack of confidence (Al-Kubaisy et al, 2020;Razak et al, 2017). The difference can also be related to brain composition difference (Liu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Females may feel more pressure to conform to societal expectations of being better communicators and writers than males, leading to higher levels of anxiety when it comes to writing (Al-Kubaisy et al, 2020;Cocuk et al, 2016). Likewise, females may be more likely to be perfectionists and set higher standards for themselves (Khosravi et al, 2023), and females may lack confidence in their writing abilities (Al-Kubaisy et al, 2020;Razak et al, 2017), leading to higher levels of anxiety when it comes to writing. In addition, females may be more likely to receive negative feedback on their writing (Al-Kubaisy et al, 2020), and females may be more likely to internalize negative stereotypes about their writing abilities (Rodríguez et al, 2009), leading to higher levels of anxiety when it comes to writing.…”
Section: Literature Reviewmentioning
confidence: 99%